2020
DOI: 10.7717/peerj.8436
|View full text |Cite
|
Sign up to set email alerts
|

Association of IGF1 single-nucleotide polymorphisms with myopia in Chinese children

Abstract: Purpose To investigate the association between insulin-like growth factor 1 (IGF1) single-nucleotide polymorphisms (SNPs) and myopia in a young Chinese population. Methods A total of 654 Chinese children aged 6–13 years from one primary school participated in our study and underwent a series of comprehensive ocular examinations, including cycloplegic refraction and measurements of axial length. Myopia was defined as a spherical equivalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In 2010, Metlapally et al [ 43 ] and Zidan et al [ 33 ] found that rs6214 was positively associated with any myopia/high-grade myopia after correcting for multiple testing. However, in other studies, no significant association for rs6214 was found using single marker analysis [ 27 – 32 , 34 , 35 ]. Zhuang et al [ 31 ] and Zhao et al [ 35 ] reported that rs12423791 was significantly associated with high myopia in a Chinese population.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In 2010, Metlapally et al [ 43 ] and Zidan et al [ 33 ] found that rs6214 was positively associated with any myopia/high-grade myopia after correcting for multiple testing. However, in other studies, no significant association for rs6214 was found using single marker analysis [ 27 – 32 , 34 , 35 ]. Zhuang et al [ 31 ] and Zhao et al [ 35 ] reported that rs12423791 was significantly associated with high myopia in a Chinese population.…”
Section: Discussionmentioning
confidence: 86%
“…Among these SNPs, seven were tested in at least three studies and then were included in the meta-analysis. The study subjects were Chinese [ 29 , 31 , 32 , 34 , 35 ], Japanese [ 27 , 28 ], Egyptian [ 33 ] and Polish [ 30 ] with sample sizes that ranged from 127 to 1339. The total sample size was 9546 (4596 individuals with any myopia and 4950 controls).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic association studies showed that single nucleotide polymorphism observed in IGF-1 was significantly associated with different types of myopia, including high myopia in Caucasian and Chinese populations ( 43 , 44 ).…”
Section: Factors Involved In Myopia Digital Therapeuticsmentioning
confidence: 99%
“…Experimental studies on chicken and guinea pigs revealed that various molecules if applied intraocularly or topically had an effect on an externally induced elongation of the optical axis. The list of these molecules includes dopamine and its agonists and antagonists, atropine, transforming growth factor beta (TGF-ß), fibroblast growth factor, hepatocyte growth factor, insulin-like growth factor, and amphiregulin, and other epidermal growth factor (EGF) family members [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. To further elucidate the potential association of EGF and its family members with the process of myopic axial elongation in humans, we undertook this study to examine the intraocular concentration of EGF in the aqueous humor of non-highly patients and patients with high myopia.…”
Section: Introductionmentioning
confidence: 99%